Internacionalização do ensino superior: a experiência da Universidade Estadual do Oeste do Paraná - Assenza, Marta Lúcia Alves (2018)
Faced with the phenomenon of globalization, when many of human activities apart from economy, gain the world, education acquires an important role in the current context of humanity - assuming that society seeks a fairer and a better world. University has vast share in this pursuit, in which the production of knowledge moves beyond its walls and takes over the world through the Internationalization of Higher Education. In this sense, the present project intends on, from the concepts of Internationalization of Higher Education, identifying the activities carried out at the State University Of West of Paraná (UNIOESTE) and how it is inserted in this teaching activity, which has been gaining strength, with social programs of students’ scholarships and by receiving foreign students. Through an analytical methodology of data and qualitative character, it is sought to identify, with a bibliographical and documentary research, the existing activities that characterize the Internationalization. What activities are performed and the degree of importance of each activity and also, if UNIOESTE has effectively executed Internationalization in the period of 1996 to 2016, in the aspects presented by the authors towards the subject.